The sustainable development of the European logistics industry: an analytic approach at micro and macroeconomic levels - Flavio Boscacci (European Regional Science Association (ERSA), 2004)
A large re-structuring process is running in the European logistics market. The main driving forces come from the globalisation of the Economy, encouraged by the decrease of the unit transportation costs and by the contemporaneous upgrading of the labour level costs and the legal environmental costs. So, a good logistics system has become a must for the competition at both micro and macro-economic levels. Given the effectiveness of the single deliveries of goods, the main problem is to increase efficiency of the logistics services. From the micro-economic point of view, the problem consists in minimising the costs of the production processes of goods management services. In Europe, in particular, we are watching a large re-organisation of the logistics enterprises and of their territorial networks to achieve the best scale and scope economies of production. At the macroeconomic level, the problem is to estimate the rate of the logistics services on the GDP. In this paper we investigate the European logistics market transformations both from microeconomics and macroeconomics points of view. Thus, we will analyse the investments of the logistics sector as well as the logistics supply value as a component of GDP and its contribution to the International balance of commerce. Moreover, the infrastructures system quality (railways, roads, telecommunication, ports, airports, etc.) will be considered as a base asset for the reduction of the private costs of service production and as a territorial resource for the sustainable vehicles circulation.
Keywords: 330